Developing and Assessing Options for the Global SOF Network - Szayna, Thomas S.; Welser IV, William (RAND Corporation, 2023)
U.S. Special Operations Command’s Global SOF Network vision calls for a distributed overseas posture for Special Operations Forces (SOF) as part of a new approach to respond to and deter threats. RAND researchers developed implementation options by creating and applying an analytically rigorous methodology. They also investigated the possible need for changes to command and control arrangements or funding and budgeting processes.